Cooperative males reduce incubation in response to cues of female–female competition. (23rd December 2013) - Dey, Cody J.; O'Connor, Constance M.; Balshine, Sigal; Quinn, James S.; Schoech, Steve
<x xml:space="preserve">Abstract</x> Social groups of the joint‐laying Pukeko Porphyrio porphyrio melanotus typically contain one or two breeding females. Male Pukeko mated to two females father more offspring and therefore benefit from this mating arrangement; however, primary females should not prefer this system, because fewer eggs hatch per female in the larger joint clutches. Here, we investigated male response to simulated egg destruction, a common female competitive tactic observed in other joint‐laying species. In response to egg removal, males reduced the consistency of their incubation and in some cases nests were abandoned. Such decreases in paternal effort could eliminate any putative advantage gained by a female that destroys the eggs of a co‐nester. Our study demonstrates facultative adjustments in paternal care in a joint‐laying species and suggests that primary females may be limited in their ability to monopolize reproduction.